A muscle-specific intron enhancer required for rescue of indirect flight muscle and jump muscle function regulates Drosophila tropomyosin I gene expression. - Schultz, J R (1991)
The control of expression of the Drosophila melanogaster tropomyosin I (TmI) gene has been investigated by P-element transformation and rescue of the flightless and jumpless TmI mutant strain, Ifm(3)3. To localize cis-acting DNA sequences that control TmI gene expression, Ifm(3)3 flies were transformed with P-element plasmids containing various deletions and rearrangements of the TmI gene. The effects of these mutations on TmI gene expression were studied by analyzing both the extent of rescue of the Ifm(3)3 mutant phenotypes and determining TmI RNA levels in the transformed flies by primer extension analysis. The results of our analysis indicate that a region located within intron 1 of the gene is necessary and sufficient for directing muscle-specific TmI expression in the adult fly. This intron region has characteristics of a muscle regulatory enhancer element that can function in conjunction with the heterologous nonmuscle hsp70 promoter to promote rescue of the mutant phenotypes and to direct expression of an hsp70-Escherichia coli lacZ reporter gene in adult muscle. The enhancer can be subdivided further into two domains of activity based on primer extension analysis of TmI mRNA levels and on the rescue of mutant phenotypes. One of the intron domains is required for expression in the indirect flight muscle of the adult. The function of the second domain is unknown, but it could regulate the level of expression or be required for expression in other muscle.